Ostracoda (Crustacea) biodiversity: a taxonomic and functional approach. - Ferreira, Vitor Góis (2023)
The impacts of human actions, as deforeations, pollution and introduction of species have been causing negative effects on the environment. The extinction of species, and change of distribution range, are some of them, especially in the aquatic environment were it is observed a hogh richness compared to its extension. Thus, the knowledge about biodiversity is of extreme importance conservation of ecosystems. Ostracods are one example of a group constantly affected but ill studied. It was performed a revision of Cyprettinae s.l. from circumtropical regions, using morphological taxonomy. The first step in the revision of Cyprettinae s.l. was redescribe the type species of Cypretta Vavra, 1895 from the original type material, discuss the morphology and diagnosis of the genus. After that it was described two new species from Pseudocypretta Klie, 1932 genus from South Africa and Brazil; and described a new genus and four new species from Brazil. With the redescription of the type species of the Cyprettathe diagnosis characters for the species and genus were delimited. Analyzing the features of the new species of Pseudocypretta this genus was moved from the Cyprettinae subfamily to the Cypridopsinae subfamily, and expanded the distribution of this genus to the Afrotropical and Neotropical regions. The new genus and new species were recorded from the four main floodplain of Brazil and were designated to the Cyprettinae subfamily. Both Cypretta, Pseudoypretta and new genus are characterized by presence of septas in its valves, however they vary in level of development (complete or incomplete) and disposition along the margins of the valves. Using a database of ostracods distribution and ecological niche modelling (ENMs) the effects of climate change were evaluated to the functional diversity of ostracods in the South Cone of South America, in the moderate-optimistic and pessimistic scenarios of 2050 and 2080. It is projected that the ostracod functional diversity will suffer a gradual reduction in 2050 and 2080on bothscenarios of carbon emission, but especially in the pessimistic scenario of 2080. The results highlight the importance of evaluate the functional diversity for ostracod conservation, since several areas marked to have low taxonomic richness supported intermediate and high levels of functional diversity.